An investigation of innovative strategies in underwater soft robotics - Shahid A. Hasib; Muhammad Majid Gulzar; Sumaiya Rahman Oishy; Muhammad Maaruf; Salman Habib; Adnan Shakoor (Engineering Science and Technology, an International Journal, 2025)
Soft robotics has become a transformative technology for underwater applications, providing distinct advantages such as flexibility, adaptability, and safe interactions with fragile environments. This review offers a comprehensive analysis of the latest developments in actuation mechanisms, intelligent materials, fabrication methods, and control strategies specific to underwater soft robotics. It highlights key challenges like material degradation, energy efficiency, and control in dynamic aquatic conditions. Noteworthy advancements include bio-inspired actuators that mimic marine life and the integration of smart materials to enhance responsiveness and durability. Unlike previous reviews that focused on general aspects, this paper emphasizes cutting-edge soft actuator technologies and interdisciplinary applications that address challenges in complex aquatic environments with greater precision. Additionally, innovative fabrication techniques such as 3D printing and soft lithography are explored, revolutionizing the design and construction of underwater robots. The review also identifies critical gaps in current research and suggests future directions, stressing the importance of interdisciplinary approaches to tackle the complexities of underwater environments. It serves as a valuable resource for researchers and professionals seeking to advance the field and its applications.